2011
DOI: 10.1590/s1678-77572011000200013
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and non-nutritive sucking patterns related to the prevalence of anterior open bite in primary dentition

Abstract: ObjectiveNutritional, immunological and psychological benefits of exclusive breastfeeding for the first 6 months of life are unequivocally recognized. However, mothers should also be aware of the importance of breastfeeding for promoting adequate oral development. This study evaluated the association between breastfeeding and non-nutritive sucking patterns and the prevalence of anterior open bite in primary dentition.Material and MethodsInfant feeding and non-nutritive sucking were investigated in a 3-6 year-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
2
28

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(120 citation statements)
references
References 15 publications
4
86
2
28
Order By: Relevance
“…Although the present study did not observe an association between breast feeding and AOB, a previous study demonstrated that extending breastfeeding for 12 months was associated with a 3.7 times lower chance of having anterior open bite (30). It is possible that this result did not present a statistical significance due to the fact that 88% of the sample had extended breastfeeding.…”
Section: Discussioncontrasting
confidence: 92%
“…Although the present study did not observe an association between breast feeding and AOB, a previous study demonstrated that extending breastfeeding for 12 months was associated with a 3.7 times lower chance of having anterior open bite (30). It is possible that this result did not present a statistical significance due to the fact that 88% of the sample had extended breastfeeding.…”
Section: Discussioncontrasting
confidence: 92%
“…These results have contributed for a discussion about pacifier use as a consequence of difficulties found by mother and infant to maintain breastfeeding as a source of satisfaction of non-nutritive sucking, which was also presented by Silva e Guedes 22 . The inverse relationship between longer breastfeeding time and lower frequency of non-nutritive sucking habits was also shown 6,15 , whereas Carrascoza et al 16 associated the lower frequency of pacifier use with the presence of exclusive breastfeeding at the end of the first month of life, at the moment of hospital discharge and at the age of six months old.…”
Section: Discussionmentioning
confidence: 91%
“…The lower the breastfeeding time, the higher the possibility of introducing sucking habits 6,15,16 . Studies on the acquisition and extension of pacifier sucking habits in preterm infants are scarce in the relevant literature, showing frequency of 45.7% in the first six months of life 17 and significant association to premature birth 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Varios estudios han reportado la asociación existente entre los hábitos alimenticios, lactancia materna y no materna, y el desarrollo de maloclusiones en dentición decidua (28)(29)(30)(31)(32)(33)(34)(35). Tanto a la lactancia materna como a la no materna se les han asociado con una mayor probabilidad de desarrollo de mordida cruzada (36,37).…”
Section: Lactancia No Materna Y El Riesgo De Maloclusiónunclassified